Factors associated with childhood undernutrition in poor Ethiopian households: Implications for public health interventions - Biniyam Sahiledengle; Kingsley Emwinyore Agho; Yohannes Tekalegn; Degefa Gomora; Daniel Atlaw; Demisu Zenbaba; Fikreab Desta; Zinash Teferu; Girma Beressa; Telila Mesfin; Yordanos Sintayehu; Lillian Mwanri (PLoS ONE, 2025)
Background Childhood undernutrition is a significant public health concern linked to poverty. Despite the persistent high burden of childhood undernutrition in Ethiopia, there is a lack of robust evidence identifying factors associated with undernutrition in under-five children from poor households in the nation. This study aimed to identify the determinants of childhood undernutrition among children living in poor households in Ethiopia. Methods The 2005, 2011 and 2016 Ethiopian Demographic and Health Surveys were combined, and analysis was restricted to children aged 0–59 months from poorer and poorest households, yielding a weighted sample of 12,466 analysed. The adverse nutritional status indicators of child nutritional status: height-for-age z-scores (HAZ), weight-for-age z-scores (WAZ), and weight-for-height z-scores (WHZ) were the outcomes of interest. The child’s HAZ, WHZ, and WAZ were below -2 standard deviations (SD) were categorized as binary and into stunted, wasted, and underweight, respectively. Multilevel mixed-effect logistic regression analyses were conducted to examine factors associated with childhood undernutrition in poor households. Results The prevalence of stunting, wasting and underweight among children aged 0–59 months in poor households was 47.5% (95% CI: 46.5–48.4), 12.7% (95% CI: 12.1–13.3), and 32.8% (95% CI: 31.9–33.7), respectively. The most significant factors positively associated with stunting, wasting, and being underweight comprised of male gender, younger age, having diarrhea two week before each survey, children perceived as smaller by their mothers (stunted and wasted only), children of uneducated mothers (stunting and underweight only), maternal short stature (stunting and underweight only), and children from households having unimproved sanitation facility (stunting and underweight only). The odds of wasting were significantly higher among children who lived in urban areas, children from female-headed households and those children who had fever two weeks before each survey. Conclusion Child undernutrition in poor Ethiopian households is significantly higher than the national average, highlighting a critical public health issue. Urgent intervention focusing on the identified risk factors, such as sanitation, maternal education, and childhood diarrhea is needed, to improve child nutrition and well-being in disadvantaged households.